Analog Desires: On Stranger Things and the Logics of Nostalgia - Willis, Louis-Paul (Intermédialités / Intermediality, 2022)
This paper examines the relation between Stranger Things (Netflix, 2016–) and the omnipresence of nostalgic tropes within current mediascapes. Nostalgia for the 1980s is already a well-examined subject within film and media studies, yet there remains much to say about the ties between nostalgia and desire. As with any desire considered from a psychoanalytic standpoint, nostalgia is focused on an impossible object that is conceived in retrospect. After comparing the object of nostalgia with the functioning of the object-cause of desire as it is conceptualized in psychoanalytic thought, this paper argues that the nostalgic desire expressed within the series is situated around the very shift from the analog to the digital. It is argued that nostalgia within Stranger Things emerges from the remediation of analog media and technologies, and that its relation to desire emanates from the very lack that is retrospectively situated at the heart of digital media.